2022
DOI: 10.31729/jnma.7579
|View full text |Cite
|
Sign up to set email alerts
|

Raised D-dimer among Admitted COVID-19 Patients in a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Patients with COVID-19 are characterised by abnormal levels of inflammatory biomarkers. Elevated D-dimer in COVID-19 patients is associated with increased mortality. This study aimed to find out the prevalence of raised D-dimer among COVID-19 patients in a tertiary care centre. Methods: This descriptive cross-sectional study was conducted in COVID-19 unit of a tertiary care centre from 23 January 2021 to 19 June 2021. The ethical approval was taken from the Institutional Review Committee (Referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The screening of effective biomarkers, patient classification, clinical management, and prevention of serious complications are essential in combating the progression of COVID-19, reducing severe and fatal outcomes, and improving treatment strategies [11]. Prominent biomarkers such as D-dimer, Serum ferritin, C-reactive protein (CRP), Interleukin-6, Lactate dehydrogenase (LDH), and HRCT have been identified for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The screening of effective biomarkers, patient classification, clinical management, and prevention of serious complications are essential in combating the progression of COVID-19, reducing severe and fatal outcomes, and improving treatment strategies [11]. Prominent biomarkers such as D-dimer, Serum ferritin, C-reactive protein (CRP), Interleukin-6, Lactate dehydrogenase (LDH), and HRCT have been identified for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…From this study, we observed quantitative variation of phytoconstituents (ascorbic acid, total phenol, and flavonoid content) in citrus species grown in different regions of Western Nepal. Phytoconstituents, like ascorbic acid flavonoids, phenols, alkaloids, etc., are being used in allopathic and also found to be used traditionally as ethnomedicines for antiviral properties like in COVID-19 treatment [19][20][21]. The extraction of the juice of citrus fruit was done using ethanol as a solvent, and the extractive value was found to be higher in citrus species collected from Nawalparasi.…”
Section: Discussionmentioning
confidence: 99%